2019
DOI: 10.3390/polym11010172
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Crimpness of Animal Hairs via Water-Stimulated Shape Fixation for Regulation of Thermal Insulation

Abstract: Animals living in extremely cold plateau areas have shown amazing ability to maintain their bodies warmth, a benefit of their hair’s unique structures and crimps. Investigation of hair crimps using a water-stimulated shape fixation effect would control the hair’s crimpness with a specific wetting-drying process thereafter, in order to achieve the regulation of hair thermal insulation. The mechanism of hair’s temporary shape fixation was revealed through FTIR and XRD characterizations for switching on and off t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It was proposed that hair coat and its shape has a considerable impact on conduction, convection, water vapor diffusion and radiative transfer between skin surface and the external environmental temperature 15 . In particular, a curled hair shape was proposed to exhibit a beneficial property for thermal insulation in cold temperature conditions to retain body heat 16 as well as for cooling under hot temperature 17 .…”
Section: Selection For Desirable Traits and Breed-specific Phenotypesmentioning
confidence: 99%
“…It was proposed that hair coat and its shape has a considerable impact on conduction, convection, water vapor diffusion and radiative transfer between skin surface and the external environmental temperature 15 . In particular, a curled hair shape was proposed to exhibit a beneficial property for thermal insulation in cold temperature conditions to retain body heat 16 as well as for cooling under hot temperature 17 .…”
Section: Selection For Desirable Traits and Breed-specific Phenotypesmentioning
confidence: 99%
“…Animal wool fiber has been traditionally considered for producing good thermal insulation of textiles for thousands of years 13 . Controllable crimpness of animal hairs via water‐stimulated shape fixation was investigated on the regulation of thermal insulation and the study indicated that thermal insulation of hairs was regulated by managing the hair temporary crimps 14 . Sintered porous balls from rice husks were investigated for thermal insulation in iron and steel industries and the ball shape porous structure has increased insulation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, shape memory polymers (SMPs) have gained attention because of their responsive manners to various types of stimuli (including water, electrical, heat, and pH) [1]. Visually, SMPs can recover their original shapes from temporarily deformed shapes when exposed to appropriate environmental stimuli [2,3,4], namely, the shape memory effect (SME), which is due to their unique molecular structures. According to a proposed structural model of SMP, a polymer with SME should be composed of molecular switches and netpoints [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Visually, SMPs can recover their original shapes from temporarily deformed shapes when exposed to appropriate environmental stimuli [2,3,4], namely, the shape memory effect (SME), which is due to their unique molecular structures. According to a proposed structural model of SMP, a polymer with SME should be composed of molecular switches and netpoints [3,4,5]. When exposed to some predetermined external stimuli, the molecular switches play an important role in dominating the shape fixity and recovery, which may be crystalline phase or amorphous polymer chains.…”
Section: Introductionmentioning
confidence: 99%